STRATEGI: DIMENSI, FASET, KONTEKS, DAN DOMAIN (Fokus Ekonomi, 2008)
There are four fundamental elements in strategy framework that reflect company’s strategic profile, i.e., dimension, facet, context, and domain. The essence of strategy is the choice of actions that different from those of competitors. Thus, the primary role of strategy is not to respond opportunities and threats passively, but to adapt itself to the change of its external environment actively. Four critical dimensions of strategy existence are planning, pattern, position, perspective, and tactic. Two domains of strategy are content and process which related of each other. In content issues reflected “what strategy is supposed to be chosen by organization”, while in process issues implied “how organization suppose to chose and implement its strategy”. Lastly, the key element of strategy framework is organization performance. In the context of strategy content, there are two determinant which determine organization performance i.e., strategic stance and strategic action. Strategic stance is defined as the rate in which organization exists at the position of prospector, defender, or reactor, whereas strategic action is emphasizing of market change, service, income, external relation, and organization characteristics. Key words: strategic profile, dimension, facet, context, domain, strategic stance,  strategic action